Differentiated National Education: Impact on Elementary Students’ Nationalistic Insight - ., Asnawi; Kenedi, Ary Kiswanto; Sahudra, Tengku Muhammad; Ramadhani, Dini; Fransyaigu , Ronald (Journal of Ecohumanism, 2024)
The lack of nationalistic insight among elementary school students served as the driving force for this study. This led to the creation of a differentiated nationalistic education learning model based on social and emotional learning that needed to be tested for effectiveness. This study sought to ascertain how elementary school children’s nationalistic insight was impacted by a differentiated national education learning model based on social and emotional learning. Two hundred elementary school pupils participated in this quasi-experimental study. Test questions were used to examine nationalistic insight. The Jamovi application was used to examine the measurement findings using an independent sample for the t-test. According to the findings, students who participated in differentiated nationalistic education based on social and emotional learning and those who attended conventional nationalistic education differed significantly in their nationalistic understanding. This finding demonstrated the impact of a differentiated national education learning model based on social and emotional learning on primary school students’ nationalistic insight. Elementary school teachers should use this research’s implications as a guide to help students develop a nationalistic insight